2009
DOI: 10.1093/scan/nsp008
|View full text |Cite
|
Sign up to set email alerts
|

In search of the depressive self: extended medial prefrontal network during self-referential processing in major depression

Abstract: Major depression is associated with an excessive self-focus, a tendency to engage oneself in self-referential processing. The medial frontal gyrus (MFG) is central to self-referential processing. This study aimed to explore the neural bases of this excessive self-focus and to disambiguate the role of the MFG in the pathophysiology of major depression. We presented 15 depressed patients and 15 healthy subjects with personality traits during functional magnetic resonance imaging and asked them to judge whether e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
178
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(204 citation statements)
references
References 38 publications
19
178
0
7
Order By: Relevance
“…Sheline et al (2010) reported hyperconnectivity with bilateral dorsal medial prefrontal cortex across the ECN, the DMN, and the DAN and proposed that these patterns of hyperconnectivity may explain impaired concentration (ECN), increased rumination, selffocus, and vigilance (DMN), and emotional, visceral, and autonomic dysregulation (DAN) in MDD. These findings converge with other reports of aberrant affective network activation at rest and during emotional tasks in MDD (Johansen-Berg et al, 2008;Mayberg et al, 1999;Smoski et al, 2009), DMN hyperactivation during emotional tasks (Sheline et al, 2009), DMN hyperconnectivity at rest in MDD (Lemogne et al, 2009), and increased task-related connectivity (Schlosser et al, 2008;Vasic et al, 2009) and decreased task-related activation (Davidson et al, 2002;Panksepp, 2010) in the ECN in MDD.…”
Section: Introductionsupporting
confidence: 90%
“…Sheline et al (2010) reported hyperconnectivity with bilateral dorsal medial prefrontal cortex across the ECN, the DMN, and the DAN and proposed that these patterns of hyperconnectivity may explain impaired concentration (ECN), increased rumination, selffocus, and vigilance (DMN), and emotional, visceral, and autonomic dysregulation (DAN) in MDD. These findings converge with other reports of aberrant affective network activation at rest and during emotional tasks in MDD (Johansen-Berg et al, 2008;Mayberg et al, 1999;Smoski et al, 2009), DMN hyperactivation during emotional tasks (Sheline et al, 2009), DMN hyperconnectivity at rest in MDD (Lemogne et al, 2009), and increased task-related connectivity (Schlosser et al, 2008;Vasic et al, 2009) and decreased task-related activation (Davidson et al, 2002;Panksepp, 2010) in the ECN in MDD.…”
Section: Introductionsupporting
confidence: 90%
“…More interestingly, there were also differences in activations between the two types of semantic judgments, with judgments about the self leading to greater activation in the MPFC than judgments about the other. An increased activation in the MPFC when reflecting on one's own traits (compared to the traits of others or to making semantic judgments) has also been observed in several subsequent studies [14][15][16][17][18][19][20][21][22][23][24][25][26] (see Fig. 1 for an illustration of the MPFC activations detected in different studies).…”
Section: Representing One's Personal Characteristics: Semantic Forms supporting
confidence: 61%
“…White circles represent the locations of peak MPFC activations detected when reflecting on one's own psychological traits relative to reflecting on the traits of others or making semantic judgements. [13][14][15][16][17][18][19][20][21][22][23]25,26,29,30 White squares represent the locations of peak MPFC activations detected when reflecting on one's own promotion goals. [38][39][40][41] when participants made judgments from their own perspective and when they made judgments from the perspective of their friend.…”
Section: Representing One's Personal Characteristics: Semantic Forms mentioning
confidence: 99%
“…CEM related dorsal mPFC responsivity may reflect a further increase in negative selfand other-referential processing in these individuals, since the mPFC is pivotal in self-referential processing [20,[48][49][50][51][52][53]. And a recent meta-analysis suggested that dorsal mPFC responsivity to social exclusion is related with enhanced social uncertainty, social distress, and social rumination [15].…”
Section: Discussionmentioning
confidence: 99%